A 31‐channel integrated "AC/DC" B0 shim and radiofrequency receive array coil for improved 7T MRI. Issue 2 (10th October 2021) - Stockmann, Jason P.; Arango, Nicolas S.; Witzel, Thomas; Mareyam, Azma; Sappo, Charlotte; Zhou, Jiazheng; Jenkins, Lucas; Craven‐Brightman, Lincoln; Milshteyn, Eugene; Davids, Mathias; Hoge, W. Scott; Sliwiak, Monika; et al.
Abstract : Purpose: To test an integrated "AC/DC" array approach at 7T, where B0 inhomogeneity poses an obstacle for functional imaging, diffusion‐weighted MRI, MR spectroscopy, and other applications. Methods: A close‐fitting 7T 31‐channel (31‐ch) brain array was constructed and tested using combined Rx and ΔB0 shim channels driven by a set of rapidly switchable current amplifiers. The coil was compared to a shape‐matched 31‐ch reference receive‐only array for RF safety, signal‐to‐noise ratio (SNR), and inter‐element noise correlation. We characterize the coil array's ability to provide global and dynamic (slice‐optimized) shimming using ΔB0 field maps and echo planar imaging (EPI) acquisitions. Results: The SNR and average noise correlation were similar to the 31‐ch reference array. Global and slice‐optimized shimming provide 11% and 40% improvements respectively compared to baseline second‐order spherical harmonic shimming. Birdcage transmit coil efficiency was similar for the reference and AC/DC array setups. Conclusion: Adding ΔB0 shim capability to a 31‐ch 7T receive array can significantly boost 7T brain B0 homogeneity without sacrificing the array's rdiofrequency performance, potentially improving ultra‐high field neuroimaging applications that are vulnerable to off‐resonance effects.